Interface structure and strain relaxation in BaTiO3 thin films grown on GdScO3 and DyScO3 substrates with buried coherent SrRuO3 layer - Chen, Y. B.; Sun, H. P.; Katz, M. B.; Pan, X. Q.; Choi, K. J.; Jang, H. W.; Eom, C. B. (AMER INST PHYSICS, 2007)
To obtain the electrical properties of strained ferroelectric thin films, bottom electrodes with lattice constants and thermal coefficients matched to both films and substrates are needed. The interface structure, strain configuration, and strain relaxation in such bilayer systems are different from those in single layer systems. Here, we report transmission electron microscopy studies of epitaxial BaTiO3 films grown on GdScO3 and DyScO3 substrates with buried SrRuO3 layers. We found that the different strain relaxation behaviors observed in the bilayer are mainly dependent on lattice mismatch of each layer to the substrate and the thicknesses of each layer.
Keywords: DISLOCATION; FERROELECTRICITY; ENHANCEMENT; EVOLUTION; SRTIO3